2011
DOI: 10.1159/000329234
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Mesenchymal Stem Cells with Oxytocin Enhances the Cardiac Repair in Ischemia/Reperfusion Injury

Abstract: Oxytocin stimulates the cardiomyogenesis of embryonic stem cells and adult cardiac stem cells. We previously reported that oxytocin has a promigratory effect on umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs). In this study, UCB-MSCs were cultured with oxytocin and examined for their therapeutic effect in an infarcted heart. UCB-MSCs were pretreated with 100 nM oxytocin and cardiac markers were assessed by immunofluorescence staining. Next, oxytocin-supplemented USC-MSCs (OT-USCs) were coculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 51 publications
(41 reference statements)
0
49
0
2
Order By: Relevance
“…OXT also has a promigratory effect on umbilical cord blood-derived mesenchymal stem cells [36]. Prolonged treatment of these cells with OXT can significantly increase the expression of connexin 43, cardiac troponin I, and alpha-sarcomeric actin when they are cocultured with cardiomyocytes [37]. Thus, OXT is potentially useful to advance embryonic stem cell development to reverse osteoporosis and repair infarction damaged cardiac tissue.…”
Section: Human Developmentmentioning
confidence: 99%
“…OXT also has a promigratory effect on umbilical cord blood-derived mesenchymal stem cells [36]. Prolonged treatment of these cells with OXT can significantly increase the expression of connexin 43, cardiac troponin I, and alpha-sarcomeric actin when they are cocultured with cardiomyocytes [37]. Thus, OXT is potentially useful to advance embryonic stem cell development to reverse osteoporosis and repair infarction damaged cardiac tissue.…”
Section: Human Developmentmentioning
confidence: 99%
“…Such results could have important consequences for cellular therapy applications, because OT-primed cells may play a supportive role by optimizing host vasculature milieu and promote healing by altering cell response to ischemia. Recently, Kim et al (10) reported the priming of human MSC with OT to enhance the cardiac repair in a rat model of ischemia/reperfusion injury. In this latter study, OT-treated MSC expressed cardiac markers, and when transplanted into rat ischemic heart, MSC reduced fibrosis and improved cardiac functional recovery.…”
mentioning
confidence: 99%
“…On day 8, average relative wound closure for UCB, BM and PB MSC treated wounds was significantly different at 58%, 42%, and 22%, respectively. Based on a histological analysis, the authors also noted that both granulation tissue and re-epithelialization of UCB MSC-treated wounds appeared to be thicker and larger than those treated with BM or PB MSCs [36]. Cumulatively, these studies (summarized in Table 2) provide evidence to support the use of MSC-based therapies for the treatment of RDEB and, although less definitively, suggest that UCB MSCs may have an advantage over MSCs isolated from other tissues.…”
Section: – Placenta-based Therapies and Epidermolysis Bullosamentioning
confidence: 99%